1981
DOI: 10.1037/0022-006x.49.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in measures of personality and family environment among Black and White alcoholics.

Abstract: The debate about black Minnesota Multiphasic Personality Inventories (MMPIs) and white norms was renewed recently. Pritchard and Rosenblatt, revewing 16 studies, claimed to find no evidence that the MMPI is racially biased. Gynther and Green, reviewing 40 studies, concluded that racial bias in the MMPI varies as a function of sampling, with bias more likely when normal blacks are compared with normal whites but not when abnormal groups are compared. No study yet published has compared black alcoholics with whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

1983
1983
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 17 publications
2
12
0
1
Order By: Relevance
“…Compared with White women, Black women rated their families of origin as more cohesive, more organized, more expressive, and lower in conflict. Although contradicting reports of no differences by race (Baer, 1999; Barnes et al, 1994; Hill & Bush, 2001), our findings corroborate reports of a sample of parents with school‐age children (Bartz & Levine, 1978), a group of heroin abusers (Penk et al, 1979), a clinical sample of alcoholic men (Patterson et al, 1981), and a suburban middle‐class sample of middle school students (Bray et al, 2000).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Compared with White women, Black women rated their families of origin as more cohesive, more organized, more expressive, and lower in conflict. Although contradicting reports of no differences by race (Baer, 1999; Barnes et al, 1994; Hill & Bush, 2001), our findings corroborate reports of a sample of parents with school‐age children (Bartz & Levine, 1978), a group of heroin abusers (Penk et al, 1979), a clinical sample of alcoholic men (Patterson et al, 1981), and a suburban middle‐class sample of middle school students (Bray et al, 2000).…”
Section: Discussionsupporting
confidence: 60%
“…Earlier studies have reported racial differences in family relationships, typically finding greater cohesion and organization and less conflict in Black families. Patterson, Charles, Woodward, Roberts, and Penk (1981), studying a clinical sample of alcoholic men, reported that Blacks described both past childhood and present adulthood family environments as more cohesive and better organized than did their White counterparts. In retrospective ratings of childhood family environments, Penk, Robinowitz, Kidd, and Nisle (1979) found that Black heroin users described greater family cohesion and organization and less conflict than did White heroin users.…”
Section: Race Differences In Family Environment Characteristicsmentioning
confidence: 99%
“…Researchers using the FES to examine black families' social climate have generally (1) used a mixed ethnic and minority sample, (2) compared clinically distressed samples of blacks and whites, or (3) interviewed only one or two femily members (Dancy & Handal, 1980Moos & Moos, 1976Patterson, Charles, Woodward, Roberts, & Penk, 1981;Penk, Robinowitz, Kidd, & Nisle, 1979). Moos and Moos (1981) found significant differences between a sample of 178 middleclass Mexican American and black families and their normative sample.…”
Section: The Social Climate Of Black Familiesmentioning
confidence: 99%
“…Gynther & Green, 1980;Pritchard & Rosenblatt, 1980). The issue of racial bias in MMPI substance abuse scales assumes particular interest because among those studies finding racial bias on the MMPI favoring lower scores for blacks, nearly all have involved alcoholics or other drug abusers (Patterson, Charles, Woodward, Roberts, & Penk, 1981;Sutker, Archer, & Allain, 1978;Zager & Megargee, 1981).…”
mentioning
confidence: 99%